The Role of Advocates in Helping Defendants in Criminal Justices Processes - Arifton, Arifton; Sambas, Nandang; Mahmud, Ade (Dinasti Research, 2025)
Every criminal, civil, and state administrative justice system, including Indonesia's, recognises the importance of legal aid. Professionals with extensive knowledge of the law provide legal aid since the idea behind it is to ensure that everyone has the chance to exercise their rights. Those who give legal assistance do so because they are committed to high ideals, such as helping people achieve economic and social equality and defending their fundamental human rights.